Transcriptome and proteomic analysis of mpox virus F3L-expressing cells - Wang, Yihao; Zhang, Junzhe; Li, Mingzhi; Jia, Mengle; Yang, Lingdi; Wang, Ting; Wang, Yu; Kang, Lumei; Li, Meifeng; Kong, Lingbao (Frontiers in Cellular and Infection Microbiology, 2024)
Background Monkeypox or mpox virus (mpox) is a double-stranded DNA virus that poses a significant threat to global public health security. The F3 protein, encoded by mpox, is an apoenzyme believed to possess a double-stranded RNA-binding domain (dsRBD). However, limited research has been conducted on its function. In this study, we present data on the transcriptomics and proteomics of F3L-transfected HEK293T cells, aiming to enhance our comprehension of F3L. Methods The gene expression profiles of pCAGGS-HA-F3L transfected HEK293T cells were analyzed using RNA-seq. Proteomics was used to identify and study proteins that interact with F3L. Real-time PCR was used to detect mRNA levels of several differentially expressed genes (DEGs) in HEK293T cells (or Vero cells) after the expression of F3 protein. Results A total of 14,822 genes were obtained in cells by RNA-Seq and 1,672 DEGs were identified, including 1,156 up-regulated genes and 516 down-regulated genes. A total of 27 cellular proteins interacting with F3 proteins were identified by liquid chromatography-tandem mass spectrometry (LC-MS/MS), and 19 cellular proteins with large differences in abundance ratios were considered to be candidate cellular proteins. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses showed that the DEGs were significantly enriched in immune-related pathways, including type I interferon signaling pathway, response to virus, RIG-I-like receptor signaling pathway, NOD-like receptor signaling pathway, etc. Moreover, some selected DEGs were further confirmed by real-time PCR and the results were consistent with the transcriptome data. Proteomics data show that cellular proteins interacting with F3 proteins are mainly related to RNA splicing and protein translation. Conclusions Our analysis of transcriptomic and proteomic data showed that (1) F3L up-regulates the transcript levels of key genes in the innate immune signaling pathway, such as RIGI, MDA5, IRF5, IRF7, IRF9, ISG15, IFNA14, and elicits a broad spectrum of antiviral immune responses in the host. F3L also increases the expression of the FOS and JNK genes while decreasing the expression of TNFR2, these factors may ultimately induce apoptosis. (2) F3 protein interacts with host proteins involved in RNA splicing and protein translation, such as SNRNP70, POLR2H, HNRNPA1, DDX17, etc. The findings of this study shed light on the function of the F3 protein.